Splicing of constitutive upstream introns is essential for the recognition of intra-exonic suboptimal splice sites in the thrombopoietin gene - Romano, Maurizio (Oxford University Press, 2001)
The human thrombopoietin (TPO) gene, which codes for the principal cytokine involved in platelet maturation, shows a peculiar alternative splicing of its last exon, where an intra-exonic 116 nt alternative intron is spliced out in a fraction of its mRNA. To characterize the molecular mechanism underlying this alternative splicing, minigenes of TPO genomic constructs with variable exon–intron configurations or carrying exclusively the TPO cDNA were generated and transiently transfected in the Hep3B cell line. We have found that the final rate of the alternative intron splicing is determined by three elements: the presence of upstream constitutive introns, the suboptimal splice sites of the alternative intron and the length of the alternative intron itself. Our results indicate that the recognition of suboptimal intra-exonic splice junctions in the TPO gene is influenced by the assembly of the spliceosome complex on constitutive introns and by a qualitative scanning of the sequence by the transcriptional/splicing machinery complex primed by upstream splicing signals.